Design Of Automatic Fire Detection and Extinguishing Devices Using Arduino - Nopriadi, Nopriadi; Fajrin, Alfannisa Annurrullah (Sinkron : jurnal dan penelitian teknik informatika, 2023)
A robot is a series of hardware and software in the form of a driving program. Robots are not only used in industry; in developed countries, robots are widely used to help with household chores. Many jobs that require a lot of energy are high-risk or dangerous, one of which is detecting and extinguishing fires. Fires can be avoided if the fire can be extinguished before it spreads. When the fire has spread, extinguishing it will be difficult and high-risk. Fires can cause huge losses of both property and lives that cannot be saved. The problem can be reduced if the source of the fire can be quickly found and extinguished. In this research, a fire extinguisher robot will be designed with an Arduino Mega 2560 and an infrared flame detector to detect the presence of fire. This robot is accompanied by an HC-SR04 ultrasonic sensor so that the robot can walk automatically without hitting obstacles because this robot aims to walk down hallways such as areas in the house or in any area that has a hallway for the robot's path. This research aims to implement Arduino for the control of the ultrasonic sensor and the movement of the fire extinguisher robot. The use of an Arduino micro-controller on the fire extinguisher robot is expected to make the robot move steadily and avoid obstacles in the hallway.